THE TRANS LEVEL CHARACTERISTICS ABOUT INFINITE SERIES - Widada, Wahyu; Herawaty, Dewi; Anggoro, Abdurrobbil Falaq; Nugroho, Khathibul Umam Z (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2019)
Infinite series is one of the difficult calculus material for students. It needs to be analyzed the cognitive activities of students to make it easier for lecturers to arrange learning plans. The purpose of this study is to describe the characteristics of the trans level about infinite series. The subject of this research was a student of Mathematics Education, one of the universities in Bengkulu. A total of 5 people were selected from 29 students based on their cognitive abilities. Subjects were interviewed based on the assignment given. Data is analyzed through its genetic decomposition. The results of the study are that subjects can coordinate other objects and processes, so that the scheme is formed about the convergence of infinite series and sequences. Conclusion: the subject is able to do thematization so that forming a mature scheme is a trance level characteristic.